MEMANFAATKAN LIMBAH PLASTIK MENJADI PAVING BLOCK - TEGUH; HARTATI; Steven ANTHONY; Bonita HIRZA; Yetty HASTIANA (Diseminasi: Jurnal Pengabdian kepada Masyarakat, 2020)
Plastic waste becomes one of the sources of environmental pollution problems. Landfill in the final landfill in Palembang, will be a serious problem if it is not sought solution. This community service is in the form of counseling and processing training of plastic waste into paving block given to the partners of the community in the location where the garbage disposal. The provision of counseling and training is expected to be the process of utilizing science and technology in the utilization of plastic waste so it is economically beneficial for the community because it has a high selling value. The implementation phase of this activity in the form of 1) establishment of partnership by determining the community, 2) fulfillment of production equipment, 3) counseling on the innovation of entrepreneurship and marketing of products, 4) training of paving block making. The result of this activity is that partners can make paving blocks from plastic waste and have entrepreneurial innovation and product marketing